Fluoride removal using capacitive deionization process employing carbon electrodes. Issue 3 (9th July 2022) - Kumar, Praween; Kushwaha, Rohit; Mohan, Devendra
Abstract: Contamination of groundwater with fluoride poses adverse health impacts for humans. This study aims to investigate the feasibility of capacitive deionization process for fluoride removal from groundwater. In this study, composition of binder content was optimized and the experiments were performed using a lab scale batch reactor. Effect of initial ionic concentration on the removal efficiency was also studied. The electrodes were also evaluated for their efficiency to remove arsenic. The maximum fluoride removal efficiency obtained was 99.1% for the PVDF content of 15% (w/w) whereas for arsenic it was only 52%. The voltage applied across the electrodes was only 1.2V. Electrodes were tested for their physical strength and their characterization was done using Scanning Electron Microscope. Sorption kinetics of the electrodes was also investigated and was found that the adsorption followed elovich model most closely.